Integrated topics in economics - Abayomi, Awujola (Kaduna, Nigeria: Joyce Graphic Printers and Publishers, 2014)
Focuses on the central core of economics as they bother on twenty first century realities.
Includes bibliographical references and index.
rua 27/02/17
Loans.
Keywords: Economics